Sanming Model of Medical Service Integration: Impact on Medical Expenditures, Service Provision, and Resource Allocation in China - Lin K; Liu X; Xiang L; Luo F (Risk Management and Healthcare Policy)
Kunhe Lin,1,* Xiao Liu,2,* Li Xiang,1 Fei Luo3 1Department of Health Management, School of Medicine and Health Management, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China; 2Department of Medical Affairs, Wuhan No. 1 Hospital, Wuhan, People’s Republic of China; 3Department of Research, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fei Luo, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, No. 1277 Jiefang Avenue, Wuhan, People’s Republic of China, Email 267115670@qq.comBackground: Fragmentation of healthcare services has been a central issue, contributing to escalating medical expenditures and service provision, thereby exacerbating the waste of limited medical resources. In response, China has introduced the Sanming Mode, a medical service integration model designed to address these challenges. This study evaluates the model’s impact on medical expenditures, service provision, and resource allocation.Methods: We conducted an interrupted time series analysis on outcome variables related to medical expenditures, service provision, and resource allocation in Sanming City. The dataset encompassed operational data from all public hospitals and community health service institutions in Sanming from January 2016 to November 2019.Results: Post-reform, the monthly medical expenditures, outpatient visits, and inpatient admissions in Sanming City shifted from a rapid growth trend to a slower growth trend, with slopes decreasing by 0.1%, 1.4%, and 0.5%, respectively. Heterogeneity analysis between hospitals and community health service institutions revealed a more pronounced slowdown in the growth rate of monthly medical expenses in community health service institutions. However, the growth rates for outpatient and inpatient visits in hospitals significantly decreased post-reform, while there was no significant change observed in community health service institutions.Conclusion: The Sanming Model represents a significant localized attempt to integrate hospital and community health services in China. It effectively curbs the rapid growth of medical expenditures and service provision, thereby reducing the consumption of basic medical insurance funds. The Model enhances the efficiency of medical resource utilization and promotes a shift in service provision from hospitals to community health service institutions, reflecting a trend in resource allocation that concentrates serious illnesses in hospitals while directing minor health issues to community health service institutions. This positive impact promotes the effective integration and rational allocation of medical resources.Keywords: medical service integration, Sanming model, health expenditures, resource allocation, healthcare efficiency, Community Health Service Institutions